Everything is Tottering: Why Philosophy of History Thrives in Times of Crisis - Paul, Herman (BMGN - Low Countries Historical Review, 2012)
The philosophy of history is unlikely to disappear in a world beset by crises. Crises, understood as anomalies in how people conceive of their past-present relationships, serve as impetuses rather than as obstacles to philosophy of history. The more societies wonder whether economic growth is endless, or whether children in the West will ever reach the prosperity levels of their parents or how growing burdens of public debt will affect the ‘social contract between the generations’, the more likely they are to rethink their inherited past-present relationships. In a sense then, philosophy is a crisis phenomenon: the genre thrives in times of uncertainty. This does not imply that philosophy of history will always be taught in academic history departments: the genre has often, not to say usually, been practiced by non-historians. Historians might want to consider though, how well they serve their societies if they allow the philosophy of history to be practiced without the critical checks and balances of professional historiography. This article is part of the forum 'Theoretical History'.